2019
DOI: 10.1103/physrevd.99.115018
|View full text |Cite
|
Sign up to set email alerts
|

Dilaton-assisted generation of the Fermi scale from the Planck scale

Abstract: In scale-invariant theories of gravity the Planck mass M P , which appears due to spontaneous symmetry breaking, can be the only scale at the classical level. It was argued that the second scale can be generated by a quantum nonperturbative gravitational effect. The new scale, associated with the Higgs vacuum expectation value, can be orders of magnitude below M P , leading to the hierarchy between the Fermi and the Planck scales. We study a theory in which the non-perturbative effect is sensitive both to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…Higgs inflation, but it can also host the non-perturbative gravitational mechanism of Electroweak symmetry breaking suggested in [57] and studied further in [58][59][60]. Once all particles of the Standard Model are included, however, the Palatini formulation of gravity is no longer appropriate.…”
Section: Jhep10(2020)177mentioning
confidence: 99%
“…Higgs inflation, but it can also host the non-perturbative gravitational mechanism of Electroweak symmetry breaking suggested in [57] and studied further in [58][59][60]. Once all particles of the Standard Model are included, however, the Palatini formulation of gravity is no longer appropriate.…”
Section: Jhep10(2020)177mentioning
confidence: 99%
“…Quantum tunnelling through an energy barrier has an exponentially small probability to occur in the semi-classical approximation. The smallness of some numbers, for example the ratio among the Higgs vacuum expectation value and the Planck mass, may be viewed in these terms (thus alleviating the hierarchy problem [39][40][41][42][43]), as…”
Section: Higher-order Kinetic Termsmentioning
confidence: 99%
“…The singularity drives W to infinity. It has been shown that a possible way to make it finite is to add higher order kinetic terms (∂ψ) n , n > 2, to the Lagrangian [39][40][41][42][43]. Another application of higher-derivative terms to solve the hierarchy problem is addressed in [55] regarding the agravity theory [56].…”
Section: Higher-order Kinetic Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the latter theories may provide the appropriate language to address yet another fine-tuning puzzle of the Standard Model: the gauge hierarchy problem. It has been argued that the smallness of the Higgs mass as compared to the Planck scale may be the consequence of scale/conformal symmetry [62,32] in combination with no particle thresholds between the electroweak and Planck scales [63,27], 3 and the presence of nonperturbative gravitational effects operative at very high energies [65][66][67][68].…”
Section: Intoduction and Motivationmentioning
confidence: 99%